The Handbook of global energy policy - Goldthau, Andreas (Wiley-Blackwell, 2013)
This is the first handbook to provide a global policy perspective on energy, bringing together a diverse range of international energy issues in one volume. Maps the emerging field of global energy policy both for scholars and practitioners; the focus is on global issues, but it also explores the regional impact of international energy policies. Accounts for the multi-faceted nature of global energy policy challenges and broadens discussions of these beyond the prevalent debates about oil supply. Analyzes global energy policy challenges across the dimensions of markets, development, sustainability, and security, and identifies key global policy challenges for the future. Comprises newly-commissioned research by an international team of scholars and energy policy practitioners